(untitled) - Zhu, Lei (Hoboken, N.J., 2012)
This book will appeal to scientists and engineers who are concerned with the design of microwave wideband devices and systems. For advanced (ultra)-wideband wireless systems, the necessity and design methodology of wideband filters will be discussed with reference to the inherent limitation in fractional bandwidth of classical bandpass filters. Besides the detailed working principles, a large number of design examples are demonstrated, which can be easily followed and modified by the readers to achieve their own desired specifications.
Keywords: Broadband communication systems,Hệ thống thông tin băng thông